Depressive symptoms and mortality-findings from Helsinki birth cohort study - Eriksson Mia D.; Eriksson Johan G.; Korhonen Päivi; Koponen Hannu; Salonen Minna K.; Mikkola Tuija M.; Kajantie Eero; Wasenius Niko S.; von Bonsdorff Mikaela; Kautiainen Hannu; Laine Merja K. (Wiley, 2022)
Background: Individuals with depression and depressive symptoms have a higher mortality rate than non-depressed individuals. The increased comorbidity and mortality associated with depression has remained largely unexplained. The underlying pathophysiological differences between depressive subtypes, melancholic and non-melancholic, may provide some explanation to this phenomenon.
Methods: One thousand nine hundred and ninety five participants (mean age 61 years) from the Helsinki Birth Cohort Study were recruited for this prospective study and followed up for a mean of 14.1 years. Information regarding medical history, lifestyle, and biochemical parameters were obtained. Depressive symptoms were assessed using the Beck Depression Inventory. Standardized mortality ratios were calculated.
Results: Participants were followed up for a total of 28,044 person-years. The melancholic depressive group had an increased adjusted risk of mortality [HR 1.49 (95% CI: 1.02-2.20)] when compared to the non-depressive group. Comparing mortality to the whole population of Finland using standardized mortality ratios (SMR) both the non-melancholic [1.11 (95% CI: 0.85-1.44)] and melancholic depressive [1.26 (95% CI: 0.87-1.81)] groups had higher mortality than the non-depressive group [0.82 (95% CI: 0.73-0.93)].
Conclusions: Melancholic depressive symptoms are most strongly related to a higher mortality risk.